PEMIKIRAN ALI SYARI’ATI TENTANG IMAMAH - Agustina Damanik (Institut agama islam negeri Padangsidimpuan, 2016)
This research moved from one of the Shiite leaders are fairly well known and influential in religious thought among Shi'ite, namely Ali Syariati. He is one of the thinkers who seek to understand Islam from the sociological point of view, not only from the standpoint of normative. One of the characteristic of the Shi'ite doctrine is the Imamat (leadership) concept, which is a sensitive issue and a long debate in the history of cross pentig in Islam. Shiites come since the early days of Islam was born, which until now one of the schools that still exists and continues.In this study the authors will discuss Ali Syariati’s thought about the concept of the Imamah. This study is a research library (library research) try to decipher Ali thinking about the problem Imamah (leadership) using the method of historical research, which melipputi beberapatahap, namely heuristic, interpretation, and last histrografi. The results showed that according to Ali, Islam is not a religion that hanyamemperhatikan spiritual and moral aspects or just antrata servant relationship with the creator of universe (Hablu min Allah), but more than that, Islam is an ideology of emancipation and liberation. He believes that Islam as a school of sociology of science should function as a revolutionary force to liberate oppressed people, both culturally and politically.Imamah is a progressive and revolutionary leadership that can guide man and to build a society on the foundation of a true and strong, which will lead to the awareness, growth, and independence in making decisions. Imamate is a manifestation of